Mosque Decoration between Acceptance and Rejection - Omer, Spahic (Islamic Studies, 2015)
This paper discusses the subject of mosque decoration and some of the measures which determine its acceptability or otherwise. Indeed, the matter is a sensitive and double-edged one. Thus, the paper presents an objective, balanced and scientific account of the theme, steering clear of the sentimental aspects of the evidences often put forth by both the proponents and opponents of mosque decoration. The paper is divided into the following sections: 1) The legitimacy of decoration, 2) The function of mosques vis-a-vis their decoration, 3) Broad guidelines that regulate mosque decoration, 4) Decorating the mihrab and the qiblah wall in mosques.